Analysis of carbohydrates content in the plant components of antidiabetic herbal mixture by GC-MS - Alona Savych; Maryna Duchenko; Yulia Shepeta; Alexandra Davidenko; Olha Polonets (Pensoft Publishers, 2021)
Medicinal plants and their combinations due to the wide range of biologically active substances can influence on various links of the pathogenetic mechanism of development of diabetes mellitus and its complications. One of such combinations is an antidiabetic herbal mixture (Urticae folia, Rosae frucrus, Myrtilli folia, Menthae folia and Taraxaci radices) with established hypoglycemic, hypolipidemic, antioxidant, hepatoprotective, pancreatoprotective activity in previous pharmacological study in vivo. Thus, the aim of this study was to identify and establish the content of carbohydrates in free and bound form in the plant components of antidiabetic herbal mixture. The carbohydrates were separated by gas chromatography-mass spectrometry after conversion into volatile derivatives as aldononitrile acetate. The monomeric composition of polysaccharides was studied after their hydrolysis to form monosaccharides and polyalcohols. The results of the quantitative study showed that the predominant carbohydrate in free form was saccharose in Urticae folia, L-fructose in Myrtilli folia, Rosae frucrus, Taraxaci radices and Menthae folia, L-glucose in Rosae frucrus. Concerning the determination of monomers of polysaccharides after hydrolysis, L-glucose prevailed in all plant components of antidiabetic herbal mixture. The chromatographic study revealed a number of polyalcohols that are important for the treatment and prevention of progression of diabetes mellitus and its complications, namely, mannitol and myo-inositol.